Exploring the link between being exposed to violence as a child and suffering or perpetrating intimate partner violence throughout life: scoping review protocol (Research, Society and Development, 2022)
The hypothesis of intergenerational transmission of violence refers to the assumption that children exposed to family violence by their caregivers are more likely to reproduce violent behavior with their spouses during adulthood. This article aims to describe the protocol for a scoping review on the relationship between exposure to childhood violence and lifelong suffering/perpetuating intimate partner violence. The structure being followed is Extension for Scoping Reviews (PRSMA-ScR) from the Joanna Briggs Institute (JBI) and will involve searching for information in thirteen indexed and gray literature databases that will be searched with MESH terms, DECS, and keywords from the bank's insertion day until May 2022 in Portuguese, English, and Spanish. The selection of studies and the extraction of data into the spreadsheet will be double-blind, accompanied by a third researcher who will monitor the similarity graph and act as a judge when there is disagreement. The inclusion criteria follow the Population, Concept, and Context (PCC) structure. The studies will be mapped in 2 stages: stage 1 has a descriptive focus and seeks the contribution of the largest number of studies; step 2 will involve additional exclusion criteria and will analyze quality in order to identify successful methodological pathways. The results will be presented in a thematic analysis.